Association Between Spinal Cord Stimulation and Top-Down Nociceptive Inhibition in People With Failed Back Surgery Syndrome: A Cohort Study. Issue 7 (27th March 2019) - Goudman, Lisa; Brouns, Raf; De Groote, Sander; De Jaeger, Mats; Huysmans, Eva; Forget, Patrice; Moens, Maarten
Abstract: Background: Descending nociceptive inhibitory pathways often malfunction in people with chronic pain. Conditioned pain modulation (CPM) is an experimental evaluation tool for assessing the functioning of these pathways. Spinal cord stimulation (SCS), a well-known treatment option for people with failed back surgery syndrome (FBSS), probably exerts its pain-relieving effect through a complex interplay of segmental and higher-order structures. Objective: To the best of our knowledge, no clinical studies have thoroughly investigated the associations between SCS and CPM. Design: This was a prospective cohort study in people with FBSS. Methods: Seventeen people who had FBSS and were scheduled for SCS were enrolled in this study. The CPM model was evaluated at both sural nerves and was induced by electrical stimulation as the test stimulus and the cold pressor test as the conditioning stimulus. Results: Before SCS, less than 30% of the participants with FBSS showed a CPM effect. Significant increases in the electrical detection threshold on the symptomatic side and the nonsymptomatic side were found. On the symptomatic side, no differences in the numbers of CPM responders before and after SCS could be found. On the nonsymptomatic side, more participants showed a CPM effect during SCS. Additionally, there were significant differences for CPM activation and SCS treatment. Limitations: Limitations were the small sample size and the subjective outcome parameters in the CPM model. Conclusions: This study revealed a bilateral effect of SCS that suggests the involvement of higher-order structures, such as the periaqueductal gray matter and rostroventromedial medulla (key regions in the descending pathways), as previously suggested by animal research.